2003
DOI: 10.1159/000070771
|View full text |Cite
|
Sign up to set email alerts
|

Labyrinth Anesthesia – A Forgotten but Practical Treatment Option in Ménière’s Disease

Abstract: The aim of this study was to determine the efficiency of labyrinth anesthesia – the intratympanic instillation of lidocaine – in the treatment of Ménière’s disease and to recall a forgotten method. Twenty-four patients (15 male, 9 female), aged from 19.7 to 80.6 years (mean: 47.8 years) with the clinical diagnosis of unilateral Ménière’s disease who underwent labyrinth anesthesia in our department were included in this retrospective study. After local anesthesia of the tympanic membrane, a solution of 4% lidoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…The topical treatment with kinetin normalized hyperpigmentation, improved the aged skin structure of hairless dogs, at the same time, had no adverse effects on the skin of hairless dogs, and showed that this agent was a safe chemical for long-term application [72].…”
Section: Kinetin Propertiesmentioning
confidence: 82%
“…The topical treatment with kinetin normalized hyperpigmentation, improved the aged skin structure of hairless dogs, at the same time, had no adverse effects on the skin of hairless dogs, and showed that this agent was a safe chemical for long-term application [72].…”
Section: Kinetin Propertiesmentioning
confidence: 82%
“…Transtympanic instillation of a solution of 4% lidocaine with furfuryladenine produced a remarkable improvement in the vestibular symptoms in 87.5% of patients; 67% of these patients were free of attacks after approximately 26 months of follow up. In this work, as in the previously cited studies, lidocaine was coapplied with other drugs, in this case N(6)-furfuryladenine, which is a natural stable secondary DNA damage product with very well defined cytokine and anti-aging properties that has been linked to oxidative processes in cells [2, 12]. …”
Section: Drugs Acting On Voltage-gated Ionic Channelsmentioning
confidence: 99%
“…Analogous to Adunka et al [16], we opted not to include a control group because this study did not aim to prove one surgical technique superior to another, but solely to show the immediate and prolonged effects of tenotomy. We also do not deem it ethically sound to leave patients in need of invasive therapy untreated, so as to create a placebo control group.…”
Section: Discussionmentioning
confidence: 99%